SURVEYING CRITICAL AND SOCIAL JUSTICE-EMPHATIC ACADEMIC SOCIAL WORK IN CANADA - Wilson, Tina (Canadian Social Work Review / Revue canadienne de service social, 2021)
In this paper I raise two questions for greater collective disciplinary attention: What are the conditions of existence and the conditions of possibility of critical and justice-emphatic academic social work in the Canadian university system these days? And moreover, how might we—the “we” who read critical social theory and share a discipline—attempt to be accountable to these shifting conditions? I engage these questions with the help of critical literatures as well as an exploratory survey in which educators teaching in schools of social work in Canada were asked to identify texts and bodies of knowledge that they consider pivotal to understanding social work and social justice. Discussing educators’ responses, I identify a few nodes of thinking that would benefit from greater disciplinary attention, and I suggest one way we might focus on these shared problematics.